Multi-dimensional panel data models: The case of Borsa Istanbul - (:unkn) unknown (Peter Lang AG, 2019)
In this section, multi-dimensional panel data models are examined from a theoretical point of view and estimation methods are explained. The effects of capital structures of firms traded on Borsa Istanbul are examined based on the multi-dimensional panel data models for the period of 2003-2016 in the application section. The other firm characteristics included as explanatory variables in the analyses are firm size, liquidity and profitability. The firms in the manufacturing industry sector are grouped under seven sub-sectors of the manufacturing industry. Estimations were made based on multidimensional panel data models and the unobservable sectoral effects were also included in the models. Thus, the heterogeneity of the sub-sectors of the manufacturing industry has not been neglected. According to the findings, it has been found out that the borrowing ratio representing the capital structure affects the value of the firm positively. It has also been found out that liquidity and firm size which are under the other firm characteristics in the analyses positively affect firm value whereas firm profitability negatively affects firm value. © Peter Lang AG 2019.
Keywords: Firm value; Multi-dimensional panel data; Nested random effects